THE CRISIS OF KNOWLEDGE AUTHORITY IN QURANIC INTERPRETATION: REFLECTIONS ON THE PHILOSOPHY OF SCIENCE ON MISINFORMATION IN THE ERA OF SOCIAL MEDIA - Lestari, Rosa; Ludfi, Ludfi; Suhaili, Suhaili (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
The phenomenon of the crisis of knowledge authority in the interpretation of the Qur'an in the digital era, especially due to misinformation spread through social media, presents significant epistemological challenges. This study aims to analyze the impact of this phenomenon on the legitimacy and verification of religious knowledge, by integrating the perspective of the philosophy of science that emphasizes scientific authority in the formation of valid knowledge. The research method used is a qualitative approach with a descriptive-analytical design through the integration of epistemological theory with the dynamics of the spread of interpretations on social media. This study identifies three main aspects: first, the disintermediation of information that reduces the role of scholars and academics in guarding the authority of interpretation knowledge; second, the role of social media algorithms that accelerate the spread of invalid interpretations, including extremist and discriminatory interpretations; and third, efforts to reconstruct epistemology through strengthening scientific verification and digital literacy. This article suggests the importance of reconstructing a more transparent and inclusive interpretation verification system and increasing digital literacy to overcome misinformation, thereby rebuilding the authority of valid religious knowledge. Thus, the philosophy of science provides an important theoretical framework for understanding the crisis of the authority of religious knowledge in the digital world, as well as providing direction for rebuilding public trust in authentic and moderate interpretations.